Strategi Upselling dalam Meningkatkan Volume Penjualan Makanan Dessert di Harris Cafe Restaurant - Anisa Amallia Fadhila; Agus Solikhin; Sugiman Sugiman (Universitas Sahid Surakarta, 2022)
This research was conducted with the aim of knowing the effect of promotion, service quality and product quality on dessert sales volume at Harris Cafe Restaurant. The method used in this research is quantitative by using a sample of 100 guest respondents who enjoy dessert at Harris Cafe Restaurant. Samples were taken using purposive sampling and non-probability techniques. Data were collected using a questionnaire with descriptive data analysis and Multiple Linear Regression analysis, t test, F test using the help of SPSS version 21. The results of this study indicate that: 1) Promotion has a positive and significant effect on sales volume of dessert at Harris Cafe Restaurant, because the value of tcount is greater than ttable. 2) Service Quality has a positive and significant effect on Sales Volume of dessert at Harris Cafe Restaurant, because the value of tcount is greater than ttable. 3) Product quality has a positive and significant effect on sales volume of dessert at Harris Cafe Restaurant, because the value of tcount is greater than ttable. 4) Overall the independent variables consisting of Promotion, Service Quality, and Product Quality have a simultaneous effect on the Sales Volume of dessert at Harris Cafe Restaurant, because the F test results obtained that the Fcount value is greater than Ftable.